Characterization of PCEng2, a β-1,3-Endoglucanase Homolog in Pneumocystis carinii with Activity in Cell Wall Regulation - Villegas, Leah R. (American Thoracic Society, 2010)
Pneumocystis jirovecii pneumonia is an opportunistic fungal infection that causes severe respiratory impairment in immunocompromised patients. The viability of Pneumocystis organisms is dependent on the cyst cell wall, a structural feature that is regulated by essential cell wall–associated enzymes. The formation of the glucan-rich cystic wall has been previously characterized, but glucan degradation in the organism—specifically, degradation during trophic excystment—is not yet fully understood. Most studies of basic Pneumocystis biology have been conducted in Pneumocystis carinii or Pneumocystis murina, the varieties of this genus that infect rats and mice, respectively. Furthermore, all known treatments for P. jirovecii were initially discovered through studies of P. carinii. Accordingly, in this study, we have identified a P. carinii β-1,3-endoglucanase gene (PCEng2) that is demonstrated to play a significant role in cell wall regulation. The cDNA sequence contained a 2.2-kb open reading frame with conserved amino acid domains homologous to similar fungal glycosyl hydrolases (GH family 81). The gene transcript showed up-regulation in cystic isolates, and the expressed protein was detected within both cyst and trophic forms. Complementation assays in Eng2-deleted Saccharomyces cerevisiae strains showed restoration of the cell wall separation defect during proliferation, demonstrating the importance of PCEng2 protein. during fungal growth. These findings suggest that regulation of cyst cell wall β-glucans is a fundamental process during completion of the Pneumocystis life cycle.